Aratus’ Phaenomena beyond Its Sources - Mastorakou, Stamatina (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2020)
In this article, I compare the astronomical poem by Aratus called Phaenomena (third century bc) with the citations of a work of the same name by Eudoxus that are found in Hipparchus’ only extant work, In Arati et Eudoxi phaenomena (second century bc). I argue that, contrary to what most scholars maintain, Aratus’ poem is not a mere versification of Eudoxus’ work but a version enriched in style, language, and content. Indeed, Aratus’ Phaenomena is a paradigmatic reflection of the astronomical knowledge of the period in which it was written and a comprehensive, non-technical presentation of the celestial phenomena known in his time. It was, as I show, a very popular work, so popular that Hipparchus was moved to correct it in the hope of establishing himself as the authority in astronomy and prose as its proper medium.